Medical laboratory accreditation in a resource-limited district health centre laboratory, Addis Ababa, Ethiopia - Daniel M. Desalegn; Boja D. Taddese; Nebiyou Yemanebrhane; Mulye S. Getahun; Kumera T. Kitila; Tariku T. Dinku; Kassahun D. Asferie; Elizabeth A. Wolde; Gemechis B. Tura; Tilahun B. Mersha; Alemayhu W. Rorissa; Daniel D. Wondimagegnehu; et al. (AOSIS, 2019)
Background: Improving the quality of medical laboratory services is a high priority in many countries. However, quality management systems for laboratories in resource-limited settings are often inadequate. Objectives: This article shares the experiences, benefits and challenges of the laboratory journey towards accreditation in a primary healthcare laboratory in Addis Ababa, Ethiopia. Methods: A retrospective review of laboratory records in Addis Ketema Health Center was conducted from 2012 to 2015. The study was supplemented by observations from some of the authors of this article who worked in the laboratory. Results: The laboratory journey towards accreditation began with a baseline assessment in 2012 using the World Health Organization African Region Stepwise Laboratory Quality Improvement Process Towards Accreditation; the baseline score was 78 points (0 stars). After mentorship support, the laboratory improved to 198 points (3 stars) in 2013 and 249 points (5 stars) in 2014. The laboratory scaled up to International Organization for Standardization 15189 requirements and received limited-scope accreditation for tuberculosis sputum microscopy and hematology tests in 2015. After adopting and implementing the standards, steady improvement was observed in the reliability of the laboratory services. Lack of resources was the major challenge the laboratory encountered. Conclusion: Even though a remarkable quality performance improvement was observed over the entire process, inadequate skilled personnel was the major challenge identified in the road towards accreditation. Therefore, an appropriate, workload-based staffing structure should be developed to improve and sustain medical laboratory quality standards in resource-limited settings.